The spider family Oecobiidae in Madagascar, including four new species and a new record - Magalhães, Mayara D.f.; Santos, Adalberto J. (Zootaxa, 2018)
Four new species of Oecobiidae Blackwall, 1862 are described based on specimens collected in the Madagascan provinces of Toliara, Mahajanga and Antsiranana. Oecobius kowalskii sp. nov. and Paroecobius skipper sp. nov. are described based on male and female specimens. Paroecobius rico sp. nov. and Paroecobius private sp. nov. are described based only on females. A new diagnosis is proposed for the genus Paroecobius Lamoral, 1981 and a new record for the synanthropic Oecobius marathaus Tikader, 1962 is provided for Madagascar.